Feedback from health professionals in postgraduate medical education: Influence of interprofessional relationship, identity and power. Issue 4 (19th December 2020) - Miles, Amy; Ginsburg, Shiphra; Sibbald, Matthew; Tavares, Walter; Watling, Chris; Stroud, Lynfa
Abstract: Introduction: Capitalising on direct workplace observations of residents by interprofessional team members might be an effective strategy to promote formative feedback in postgraduate medical education. To better understand how interprofessional feedback is conceived, delivered, received and used, we explored both feedback provider and receiver perceptions of workplace feedback. Methods: We conducted 17 individual interviews with residents and eight focus groups with health professionals (HPs) (two nurses, two rehabilitation therapists, two pharmacists and two social workers), for a total of 61 participants. Using a constructivist grounded theory approach, data collection and analysis proceeded as an iterative process using constant comparison to identify and explore themes. Results: Conceptualisations and content of feedback were dependent on whether the resident was perceived as a learner or a peer within the interprofessional relationship. Residents relied on interprofessional role understanding to determine how physician competencies align with HP roles. The perceived alignment was unique to each profession and influenced feedback credibility judgements. Residents prioritised feedback from physicians or within the Medical Expertise domain—a role that HPs felt was over‐valued. Despite ideal opportunities for direct observation, operational enactment of feedback was influenced by power differentials between the professions. Discussion: Our results illuminate HPs' conceptualisation of feedback for residents and the social constructs influencing how their feedback is disseminated. Professional identity and social categorisation added complexity to feedback acceptance and incorporation. To ensure that interprofessional feedback can achieve desired outcomes, education programmes should implement strategies to help mitigate intergroup bias and power imbalance. Abstract : Miles et al reveal how interprofessional feedback to residents creates a complex social process that requires education programs to implement strategies that address intergroup bias and power imbalance.